Pn-wave attenuation tomography in Anatolia and its implications for slab break-off, mantle upwelling, and plateau uplift - Cheng, Qing-Yang; Zhao, Lian-Feng; Eken, Tuna; Xie, Xiao-Bi; Hong-Yi Li; Yao, Zhen-Xing (Copernicus GmbH, 2026)
Within the collision zone between the Arabian and Eurasian plates, the Anatolian Plateau represents an early stage in the closure of the Neo-Tethys Ocean (Teknik et al., 2025). The uplift mechanism of the Anatolian Plateau remains debated, as the primary geodynamic drivers likely vary regionally. While upper-crustal shortening dominates the northern margin of Central Anatolia, slab break-off and mantle upwelling are key along the southern and interior margins (Şengör et al., 2008; Yildirim et al., 2011). These processes are not isolated but may be geodynamically linked through subsequent shifts in plate motion and mantle flow following slab break-off. The Pn wave is a seismic phase that propagates primarily within the uppermost mantle. Its attenuation characteristics serve as a proxy for physical properties such as temperature, pressure, and water content in this region. Therefore, high-resolution attenuation tomography of the uppermost mantle using Pn waves can provide key constraints on the tectonic evolution of the Anatolian Plateau. In this study, we collected 23,830 seismic waveform data from 853 events recorded by 717 seismic stations between July 1996 and August 2025. Using a joint inversion method (Zhao et al., 2015), we constructed a broadband (0.05 - 20.0 Hz) high-resolution (1.0 1.0) Pn-wave attenuation model for the Anatolian Plateau. A prominent high-Q region observed in the southwestern part of the study area represents the Aegean Slab while a localized high-Q zone surrounded by low-Q anomalies (at approximately 36°E, 39°N) correlates with volcanism in the Central Anatolian Plateau. This work was supported by the National Natural Science Foundation of China (No. 42430306).